Arab women in the Gulf - Ramazani, Nesta (The Middle East journal, 1985)
The impact of Muslim fundamentalism on women in the Persian Gulf - Shi'i and Sunni alike - is examined through four case studies: Saudi Arabia, Bahrain, Kuwait, and the United Arab Emirates, based primarily on field interviews during various visits to the Gulf region. (DÜI-Hns)